Dynamic determinants of optimal global climate policy - Michael Grubb; Rutger-Jan Lange; Nicolas Cerkez; Pablo Salas; Ida Sognnaes (Tinbergen Institute, 2023)
We explore how optimal emission abatement trajectories are affected by dynamic characteristics of greenhouse-gas emitting systems, such as inertia, induced innovation, and pathdependency, by formulating a compact and analytically tractable model with stylized damage assumptions to derive the optimal cost-benefit pathway. Our analytic solutions highlight how simple dynamic parameters affect the optimal abatement trajectory (including the optimal current effort and the cost of delay). The conventional cost-benefit result (i.e., an optimal policy with rising marginal costs that reflects discounted climate damages) arises only as a special case in which the dynamic characteristics of emitting systems are assumed to be insignificant. More generally, our model yields useful policy insights for the transition to deep decarbonization, showing that enhanced early action may greatly reduce both damages and abatement costs in the long run.
Keywords: C61; O30; Q54; 330; abatement; DICE; energy economics; inertia; innovation; path dependence; transition